Between Shame and Fear. Review of Selected Cognitive Models of Shame in Lithuanian (On the Basis of Text and Lexicographic Data) - Bogdzevič, Monika (Vilnius University Open Series, 2020)
Linguistic and cultural research of concepts of emotional states and values finds its place among the most frequently chosen research directions in contemporary linguistics. Such popularity could be determined, on the one hand, by the desire to penetrate the complicated mental structure of human consciousness and its cognitive and cultural determinants. On the other hand, it is due to the belief in close links between language, human cognitive abilities and culture, resulting from cognitive sciences, as well as treating the research on linguistic structures and semantics of language as a tool for reaching the way of understanding and evaluating the world (cf. Bartmiński 2007; Geeraerts 2006, Evans, Green 2006). This conviction is of particular importance in the study of the lexicalization of objects and abstracts invisible to the naked eye, including emotional states. One of the main goals of the analysis of the names of emotions is revealing the way of understanding and evaluating the underlying emotional states and the experiences associated with them. In order to achieve this goal, conceptual representations of individual categories of feelings are reconstructed on the basis of the American cognitive models proposed by cognitive scientists or the base image profiles proposed by J. Bartmiński. The aim of this article is to present cognitive models and lexical units related to them, which constitute a specific borderline of emotional states of SHAME and FEAR, e. g. shame as fear of rejection, fear as a consequence of shame, etc. Thus, these are cases of linguistically certified transmissions of certain aspects of the feeling of shame and fear and their mutual convergence. The analysis presents a linguistic image of the areas of emotional experiences that constitute the periphery of the category of feelings from the family of SHAME, but not yet included in the category of feelings of FEAR in its basic sense.